2004
DOI: 10.4067/s0716-10182004000300019
|View full text |Cite
|
Sign up to set email alerts
|

Empiema pleural por Streptococcus grupo anginosus en un preescolar y revisión de la literatura: Case report and review

Abstract: Empiema pleural por Streptococcus grupo anginosus en un preescolar y revisión de la literaturaStreptococcus anginosus pleural emphyema in a child. Case report and review Left pneumonectomy in a child with congenital pulmonary malformation was performed two months prior to admission. Within one week he had high fever. Chest CT scan showed massive left pleural effusion. Both Streptococcus anginosus group and Prevotella spp. grew from the fluid obtained by pleural punction. Antimicrobial therapy was immediately i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
1
1
0
4
Order By: Relevance
“…6,14,15 Empyema in the fibrinopurulent or organizing stage should be considered an indication for surgical management. 16 The antibiotic course is usually long, with a mean duration of up to 34 days, and most SAG isolates seem to be sensitive to penicillin and cefotaxime, 10,17,18 like in our case report. Some reports indicate that patients infected by S. anginosus can be co-infected by other agents, including anaerobes, so clindamycin was added at the begin of the treatment.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…6,14,15 Empyema in the fibrinopurulent or organizing stage should be considered an indication for surgical management. 16 The antibiotic course is usually long, with a mean duration of up to 34 days, and most SAG isolates seem to be sensitive to penicillin and cefotaxime, 10,17,18 like in our case report. Some reports indicate that patients infected by S. anginosus can be co-infected by other agents, including anaerobes, so clindamycin was added at the begin of the treatment.…”
Section: Discussionsupporting
confidence: 68%
“…20 Our case appears to be one of the very few published cases reporting a pneumonia caused by S. anginosus in the pediatric age group; the only other similar case found was a report of a Chilean child. 18 However, the authors found this difficult to confirm, as the term SAG is usually used instead of the actual member of the group. Also, this agent is often responsible for other types of infection in these ages.…”
Section: Discussionmentioning
confidence: 99%
“…Los S. grupo anginosus se caracterizan por formar colonias pequeñas y pueden tener antígenos de Lancefield, A, C, G o F. Antes se les conocía como S. milleri 1 .…”
Section: Introductionunclassified
“…En cuanto a su sensibilidad antimicrobiana, el grupo Streptococcus grupo anginosus tiene una buena sensibilidad in vitro y en los reportes clínicos, a penicilina y a cefalosporinas de tercera generación, aunque están surgiendo comunicaciones de resistencia a penicilina que pueden llegar al 33% 1,5 .…”
Section: Introductionunclassified
“…Por este motivo no es sorprendente que este grupo esté compuesto por microorganismos que son muy diferentes en morfología, en reacciones hemolíticas y en participación en procesos infecciosos. A este grupo pertenecen varios subgrupos de Streptococcus y uno de estos subgrupos es el grupo anginosus (Tabla 2 del artículo de P. Pidal 1 ).…”
unclassified